Seasonal occurrence and hatching success of benthic eggs of calanoid copepods in the Bahía Blanca Estuary, Argentina - Berasategui, Anabela Anhi (2013)
The seasonal abundance and hatching success of calanoid benthic eggs were examined during the coexistence of Acartia tonsa and Eurytemora americana in the Bahía Blanca Estuary (BBE). The dormancy behaviour of eggs extracted from surface sediment layers was tested by simulating seasonal conditions during incubation. There was a greater abundance of benthic eggs of E. americana (≤8.68×106 eggs m-2) than of A. tonsa, the latter consistently showing low egg abundance (≤0.8×106 eggs m-2). The emergence of most E. americana nauplii occurred at 17°C after the experimental warming phase (refractory phase of 280 days), confirming the diapause character of these eggs. The emergence of the first A. tonsa nauplii from initial cold season samples occurred at 9-12°C after 60-70 days of incubation. However, a 180-day delay in hatching at temperatures ≥15°C was also observed in A. tonsa eggs from the last sampling days of the cold season, thus suggesting an intermediate behaviour between diapause and quiescence. The benthic egg bank in the inner zone of the BBE provides a temporary reservoir for both key copepods, thus contributing in their survival.